Darkness at dawn : the rise of the Russian criminal state - Satter, David, 1947- (Yale University Press, 2003)
Anticipating a new dawn of freedom and democracy after the disintegration of the Soviet Union, Russians could hardly have foreseen the reality of their future a decade later: a country desperately impoverished and controlled at every level by criminals. This is the story of the 1990s reform period in Russia through the experiences of individual citizens. Recounting in detail the development of a new era of oppression, journalist David Satter conveys the staggering nature of the changes that have swept Russian life, society and ways of thinking. Through the stories of people at all levels of Russian society, Satter describes fraudulent investment schemes, massive corruption, and the intrusion of organized crime everywhere. With insights derived from more than 20 years of writing and reporting on Russia, Satter considers why the individual human being there has historically counted for so little. He also offers an analysis of how Russia's post-Soviet fate was decided when a new morality failed to fill the vast moral vacuum that communism left in its wake.